Second Diagnostic Opinion by Experienced Dermatopathologists in the Setting of a Referral Regional Melanoma Unit Significantly Improves the Clinical Management of Patients With Cutaneous Melanoma - Ronchi, Andrea; Pagliuca, Francesca; Zito Marino, Federica; Argenziano, Giuseppe; Brancaccio, Gabriella; Alfano, Roberto; Signoriello, Giuseppe; Moscarella, Elvira; Franco, Renato (Frontiers in Medicine, 2021)
The diagnosis of cutaneous melanoma and melanocytic neoplasms in general is one of the most challenging fields in pathology and the reported inter-observer diagnostic agreement in the evaluation of melanocytic lesions is poor. Nevertheless, a correct histopathological diagnosis is crucial to ensure a good clinical management of the patients. The institution of multidisciplinary teams has recently modified the approach to the patients with cutaneous melanoma. Patients referred to a multidisciplinary melanoma unit after receiving a diagnosis of melanoma elsewhere are encouraged to have their histopathological diagnosis confirmed by a second opinion from the experienced pathologist of the team before any treatment is initiated. We performed a retrospective analysis on a series of 121 histopathological revisions required for melanocytic neoplasms in the context of a multidisciplinary team, in order to evaluate the effects of second diagnostic opinion on the clinical management of the patients. We defined three types of diagnostic discrepancies between the first diagnosis and the second opinion, according to the greatness of their clinical impact. Overall, the incidence of diagnostic discrepancies of any type was quite high in our series (56%). Interestingly, the second diagnostic opinion determined relevant changes in the clinical management of the patients in 33 out of 121 (27.3%) cases. This study confirms that second diagnostic opinion by expert pathologists significantly affects the course of treatment of melanoma patients and helps improving the diagnostic accuracy and clinical outcome.